2008
DOI: 10.1073/pnas.0800247105
|View full text |Cite
|
Sign up to set email alerts
|

An essential sensor histidine kinase controlled by transmembrane helix interactions with its auxiliary proteins

Abstract: Two-component signal transduction systems with membrane-embedded sensor histidine kinases are believed to recognize environmental signals and transduce this information over the cellular membrane to influence the activity of a transcription factor to which they are mated. The YycG sensor kinase of Bacillus subtilis, containing two transmembrane helices, is subject to a complicated activity-control circuit involving two other proteins with N-terminal transmembrane helices, YycH and YycI. Truncation studies of Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
94
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 26 publications
5
94
0
Order By: Relevance
“…21,22 Recent NMR structural data and the results from molecular dynamics simulations have essentially confirmed a four-helix bundle arrangement for histidine kinase transmembrane regions. 23,24 The ligand binding may control the relative orientation of these transmembrane helices. 20 Another noncrystallographic dimer in the crystal is formed by monomers with their proximal domains related by a local twofold axis.…”
Section: Dimerization Of Kind Sensor Domainsmentioning
confidence: 99%
“…21,22 Recent NMR structural data and the results from molecular dynamics simulations have essentially confirmed a four-helix bundle arrangement for histidine kinase transmembrane regions. 23,24 The ligand binding may control the relative orientation of these transmembrane helices. 20 Another noncrystallographic dimer in the crystal is formed by monomers with their proximal domains related by a local twofold axis.…”
Section: Dimerization Of Kind Sensor Domainsmentioning
confidence: 99%
“…The WalK histidine kinases of Streptococcus species have sensing domains that are structurally different from those of Bacillus, Staphylococcus, and most other species (60,84). WalK Bsu , which is typical of one class, contains two transmembrane domains flanking an extracytoplasmic domain.…”
mentioning
confidence: 99%
“…The results predicted that signal recognition by any of the extracellular domains of the sensor histidine kinase YycG or the associated proteins YycH and YycI is transmitted across the cellular membrane by subtle alterations in the positions of the helices within the transmembrane complex of the three proteins, and mutational analysis substantiated the prediction. Moreover, truncation studies of YycH and YycI demonstrated that the individual transmembrane helices of these proteins, lacking the extracellular domains, were sufficient to control YycG activity (81). What the extracellular domains of YycH and YycI are doing is still a mystery.…”
Section: An Essential Two-component System Connecting Cell Wall Growtmentioning
confidence: 99%